Meta-analysis of ultrasound-guided and traditional femoral artery puncture - Li, Jiazheng; Cao, Zhanjiang; Zhang, Tong; Zhao, Keqiang; Zhao, Junlai; Yang, Yu; Jiang, Chao; Li, Zipeng; Zhu, Rongrong; Wu, Weiwei (Frontiers in Cardiovascular Medicine, 2023)
Objective To compare the ultrasound guidance and traditional methods in femoral artery puncture. Methods We searched the databases to evaluate the rate of success on first attempt and the incidence of hematoma. The random effects model was used for performing a meta-analysis to estimate the odds ratio (ORs), mean difference (MD), and 95% confidence interval (CI). Results A total of nine articles including 2,361 patients were included in this meta-analysis. The rate of success on first attempt were 79.6% (1,289/1,619) and 54.1% (883/1,644) in patients of the ultrasound group and traditional method group, respectively [OR = 3.14 (95% CI = 2.30–4.28), combined OR value Z = 7.23 (P < 0.00001)]. The rates of incidence of hematoma in the ultrasound group and traditional puncture group patients were 1.4% (16/1,168) and 3.8% (45/1,193), respectively (OR = 0.41, 95% CI = 0.17–1.00, p = 0.05). Conclusion Ultrasound-guided femoral artery puncture has certain advantages compared with traditional puncture with regard to success on first attempt and the incidence of hematoma. Moreover, ultrasound-guided puncture reduces the incidence of hematoma in the retrograde puncture group patients.